GenZ's Purchase Decision of Branded-Preloved Clothing: Do Islamic Consumption Principles Influence Their Decisions? - Arinda, Niyara; Novi Andra, Elsa; Parsaulian, Baginda; Agung Mulyana, Cahya (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2024)
The issue of young consumer behavior in making purchasing decision to a good or service is always intriguing to analyze , particularly when considering whether their behavior aligns with Islamic values or not, especially for Generation Z (Gen Z), who are sometimes notoriously random in their actions. This study aims to estimate whether brand image, price, and fashion style affect the purchase decision of well-known brand-used clothes, and this study will elaborate in more detail on the findings from the perspective of Islamic consumer behavior. These findings will provide an important answer to whether Islamic consumption principles influence consumers' purchasing decisions. This study is quantitative research with a total of 250 respondents, which was collected using purposive sampling, which includes the younger generation of Muslims who like to shop for branded-prelove goods. The findings show that brand image, price, and fashion style are predictors of Gen Z purchasing decisions in deciding to buy branded-prelove clothing by 59.3%. A more detailed search shows that young Muslim customers still pay attention to Islamic consumption values in shopping such as rationality, simplicity, trust and honesty (Siddiq), reasonable prices, and Maslahah. This finding contributes to helping business actors design market strategies based on the behavior of the young Muslim generation. Issue tentang perilaku konsumsi muda dalam memutuskan pembelian suatu barang dan jasa selalu menarik untuk dianalisis karena pola perilaku mereka selalu dipertanyakan apakah sejalan dengan nilai-nilai Islam atau tidak, khususnya bagi Generasi Z (GenZ) yang terkadang terkenal random dalam bertindak. Penelitian ini bertujuan untuk mengestimasi apakah citra merek, harga dan gaya fashion berpengaruh terhadap keputusan pembelian pakaian bekas bermerek terkenal, dan penelitian ini akan menguraikan lebih detail temuan dalam perspektif perilaku konsumen Islam. Pertanyaan penting apakah prinsip konsumsi Islam mempengaruhi keputusan mereka dalam membeli atau tidak akan terjawab dalam temuan ini. Penelitian ini merupakan penelitian kuantitatif dengan jumlah responden sebanyak 250 orang, yang dikumpulkan dengan menggunakan purposive sampling yang meliputi generasi muda muslim yang hobi berbelanja barang-barang branded-preloved. Temuan menunjukkan bahwa citra merek, harga dan juga gaya fashion menjadi prediktor keputusan pembelian GenZ dalam memutuskan pembelian pakaian branded-prelove sebesar 59,3%. Penelusuran lebih detail menunjukkan bahwa pelanggan muda muslim masih memperhatikan nilai-nilai konsumsi Islami dalam berbelanja seperti rasionalitas, kesederhanaan, amanah dan jujur (siddiq), harga wajar, dan maslahah. Temuan ini memberikan kontribusi bagi pelaku usaha dalam merancang strategi pasar berdasarkan perilaku generasi muda Muslim.